PENGARUH STRUKTUR MODAL, PROFITABILITAS, UKURAN PERUSAHAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Marpaung, Fitri; Effendi, Syahril (LPPM Universitas Putera Batam, 2019)
Increasing the value of the company is the company's main goal, namely by increasing stock prices. Increasing company profits and maximizing the value of the company is the company's goal to improve the welfare of shareholders to maintain the survival of the company. The company's financial manager can be expected to be able to understand the factors that influence the value of the company and prosper shareholders. This research was conducted with the aim of testing and analyzing the value of the company that affects the capital structure (Debt to Equity Ratio), profitability (Return On Asset), company size (Long Size) and dividend policy (Dividend Payout Ratio) as independent and firm value as dependent . The population in this study is the automotive sector manufacturing company listed on the Indonesia Stock Exchange in the period 2013-2017 which consists of 10 companies. The sampling technique in this study used skillful sampling so that the samples obtained were as much as 50 data. The analysis in this study used descriptive statistics, classic assumption tests, multiple linear regression and hypothesis testing. From the results of this study, simultaneous capital structure, profitability, company size and dividend policy simultaneously have significant influence on firm value. Profitability and dividend policy variables have a significant effect on firm value while the capital structure and size of the company do not affect the value of the company. These results show a greater influence of provitability and dividend policy on the value of the company compared to the capital structure and size of the company.